Pengaruh Tax Avoidance dan Komite Audit Terhadap Kualitas Audit Pada Perusahaan Sub Sektor Real Estate dan Properti di Bursa Efek Indonesia (BEI) Tahun 2021 – 2024 - Mulyani, Novel; Herawati, Tuti (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze the effect of tax avoidance and audit committees on audit quality in real estate and property companies listed on the Indonesia Stock Exchange (IDX) for the period 2021–2024. Tax avoidance is measured by the Effective Tax Rate (ETR), gender diversity based on the proportion of female members, and audit quality is proxied by audit tenure (auditor rotation). Return on Assets (ROA) and company size are used as control variables. The method employed is a quantitative approach using panel data regression analysis with the Random Effect Model (REM). The sample was determined through purposive sampling, comprising 276 observations from 69 companies. The results indicate that tax avoidance has a positive and marginal effect, which is marginally significant on audit quality, while the audit committee has a negative and significant effect on audit quality. Return on Assets (ROA) and company size do not show a significant effect. This study confirms tax strategies and gender diversity as important factors in audit quality. The limitations of this study lie in its scope. Further research is recommended to expand the approach and sectors analyzed.